Design & development of an on-line multiplayer game portal - Ng, Wee San. (2010)
The development of a multi-player gaming portal will provide a platform for the community to interact with each other while having fun at the same time. Determining the games to be placed on the portal is also important. Chinese Chess, an ancient Chinese game of strategy, will be of the games that will arouse interest in a lot of gamers. Eliminating the hustle of manually setting up the chess board, this will certainly attract chess players to give it a try.